Edukasi Kesehatan Kepada Masyarakat Umum Dengan Menggunakan Metode Daring Tentang Kegawatdaruratan Positif Covid-19 Di SMAN 14 Jakarta - Erita Erita; Adventus MRL; Yanti Anggraini; Donny Mahendra (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Emergency handling of positive Covid-19 is important for the general public to know, this is because the number of deaths due to Covid-19 is very high. The purpose of this activity is to increase knowledge about Covid-19 positive emergencies. The number of participants involved as many as 120 participants. This community service activity begins with a pretest, material presentation, discussion and question and answer sessions using the Zoom meeting application, then ends with filling out a post test. Univariate and bivariate data were analyzed using paired t test. The results of this activity indicate that there is an increase in the average knowledge of respondents significantly pretest 72.06 and post test 85.09 with a significance of 0.00. This shows that the use of online methods can increase respondents' knowledge regarding the health education topics that have been given. The conclusion is that the implementation of health education using online methods can increase respondents' knowledge. It is hoped that the implementation of health education with this method can be carried out to provide information for the respondents involved.